ENVIRONMENTAL THEOLOGY IN ISLAM AND CHRISTIANITY (A study of the thoughts of Mujiyono Abdillah and Robert P. Borrong) - Nafisah Nafisah (Analisa: Journal of Social Science and Religion, 2018)
It is an undeniable fact that environmental crisis take place everywhere. It causes environmental damage in various spheres This crisis demands some awareness from the society. Therefore, it is not surprising that many activists of environment create concepts, both secular and religious nuance, to reduce the crisis. In the last few years, concept of theology of environment started to appear. This concept is relevant to be discussed, as it could bridge the secular and theological theory of environment. This research aims to look what is the environmental theology ideas of Mujiyono Abdillah and Robert P. Borrong. Also, this research identifies the similarities and differences between Abdillah’s and Borrong’s thoughts as well as how their theories could contribute to solve the environmental crisis. This is a library research and the primary source of this study is a book entitled Agama Ramah Lingkungan - Perspektif Al-Qur’an (Eco-Friendly Religion - Perspective of the Qur'an) by Mujiyono Abdillah work and Borrong’s work entitled Etika Bumi Baru (Neo-Eco Ethics). The data is analyzed by the hermeneutic theory of Hans-Georg Gadamer. The research found out that environmental theology of Abdillah includes proportional theology and meta-social-system theory. While Borrong also constructs two theories of environmental theology: theocentric inclusive theology and new earth ethic. Through these theological theories, Abdillah and Borrong expect to awaken people minds so that they could restructure their relationship with the environment. Both of the authors employ different methods. While Abdillah only utilize theology as the basis of his argument, Borrong benefits from both theology as well as biblical ethics. These theories provide an invaluable contribution to be part of the solution to the environmental crisis as they could be the alternative environmental theory which change the attitude of the community in treating the environment.